Stability analyses of deterministic and stochastic SEIRI epidemic models with nonlinear incidence rates and distributed delay - Zhang, Hong; Xia, Juan; Georgescu, Paul (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, deterministic and stochastic SEIRI epidemic models featuring a distributed latent period and general, unspecified nonlinear incidence and growth rates for the susceptible class are proposed and investigated from a stability viewpoint. By applying Lyapunov–LaSalle invariance principle, we first obtain sufficient conditions for the global stability of equilibria of the deterministic model. On the basis of this result, we subsequently derive sufficient conditions for asymptotic stability of the stochastic model. Finally, numerical simulations are given to illustrate the previously obtained theoretical framework.
Keywords: compartmental model; delay differential system; nonlinear incidence; disease relapse; global stability of equilibria; Lyapunov functional